(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
This study aims to analyze the management of football coaching at the PS Matra Team in Pasangkayu Regency, West Sulawesi Province, based on the POAC (Planning, Organizing, Actuating, and Controlling) management functions. The study used a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Research informants consisted of team administrators, coaches, players, and officials selected using a purposive sampling technique. Data analysis used the interactive model of Miles, Huberman, and Saldana, which includes data condensation, data presentation, and conclusion drawing. The results of the study indicate that the planning aspect has been carried out through the preparation of training programs and competition targets, although still constrained by budget constraints. The organizational aspect has been running with a clear organizational structure, but internal coordination is not optimal. The implementation of coaching shows routine training activities and fairly effective local player development. Supervision is carried out through routine evaluations, but the evaluation documentation system is not yet systematically organized. Supporting factors for coaching include community support, player motivation, coach experience, and local government support. The main inhibiting factors include limited funds, lack of sponsors, inadequate facilities, and suboptimal player regeneration. The research conclusion confirms that the management of PS Matra development has been running quite well, but requires strengthening of the organizational system, financing, and development of early childhood development to improve sustainable achievements.